Blood biochemical and physical parameters of crossbred barrows reared with different floor space allowances - SUBHASHISH SAHU and PANCH KISHOR BHARTI, SANDEEP KASWAN, B H MANJUNATH PATEL, SHYAMAL K MONDAL, SANJAY KUMAR (Indian Journal of Animal Production and Management, 2021)
To compare the effect of different floor space allowances on physiological status of pigs, 36 crossbred (Landrace x Desi) barrows were reared with 3 different floor space allowances {n = 4(group size) x 3(replications) = 12 each}. Group TIS (control) had floor space allowance (0.9, 1.35 and 1.8 m2/pig during weaner, grower and finisher stage) as per Indian Standards (IS: 3916-1966), while T2/3 and T1/2 treatment groups had 33% and 50% reduced floor space allocation with fixed small (n=4) group size throughout the experiment. Skin lesion score, blood parameters and back fat thickness (BFT) of pigs were estimated. Mean skin lesion score of head and ears (weaner, P